Pengaruh Model Pembelajaran Kooperatif Think Pair Share (TPS) Menggunakan Assessment For Learning Pada Prestasi Siswa Sekolah Menengah Pertama - Oki Ribut Yuda Pradana; Anwas Mashuri; Lia Septy Nirawati (Universitas Muhammadiyah Semarang, 2019)
This research was aimed to know the effect of implementing Think Pair Share cooperative learning model with the formative assessment on junior high schools student in geometry material. This study employed a quasi-experimental design with pretest-posttest1, 2, and 3. This research compares Think Pair Share using formative assessment and the conventional learning. ANOVA test was be used to analyse the effectiveness this learning. The result of ANOVA test showed that Think Pair Share with formative assessment gives different effects with conventional learning. Think Pair Share with formative assessment had encouraged students and teachers to be innovative and creative in the mathematics learning to improve the student achievement. In the future, this learning is be applied by teachers around the world.